THE CORRELATION BETWEEN SINGLE NUCLEOTIDE POLYMORPHISM С-1562Т OF THE MATRIX METALOPROTEІNAZA–9 GENE IN WOMEN WITH LEIOMYOMA AND EXTRAGENITAL PATHOLOGY - Савченко, І.М.; Гарбузова, В.Ю. (World of Medicine and Biology, 2014)
During the work, was used the venous blood of 108 women diagnosed with leiomyoma (average age was 47,82 ± 6,6 years) and the venous blood of women without it (average age was 69,75 ± 8,4 years). The С-1562Т detection of the MMP-9 gene polymorphism was conducted with the help of polymerase chain reaction method with further restriction fragments length analysis while allocating them by electrophoresis in agarose gel. Statistical data processing was carried out with the help of SPSS-17 software package. In addition, the differences were determined by χ² criterion. Values with Р
Keywords: matrix metaloproteіnaza–9; single nucleotide polymorphism; leiomyoma; COPD; gastritis